Plasticity of root anatomy during domestication of a maize-teosinte derived population. (6th September 2021) - Chen, Zhe; Sun, Junli; Li, Dongdong; Li, Pengcheng; He, Kunhui; Ali, Farhan; Mi, Guohua; Chen, Fanjun; Yuan, Lixing; Pan, Qingchun
Abstract: Maize ( Zea mays L.) has undergone profound changes in root anatomy for environmental adaptation during domestication. However, the genetic mechanism of plasticity of maize root anatomy during the domestication process remains unclear. In this study, high-resolution mapping was performed for nine root anatomical traits using a maize-teosinte population ( mexicana × Mo17) across three environments. Large genetic variations were detected for different root anatomical traits. The cortex, stele, aerenchyma areas, xylem vessel number, and cortical cell number had large variations across three environments, indicating high plasticity. Sixteen quantitative trait loci (QTL) were identified, including seven QTL with QTL × environment interaction (EIQTL) for high plasticity traits and nine QTL without QTL × environment interaction (SQTL). Most of the root loci were consistent with shoot QTL depicting domestication signals. Combining transcriptome and genome-wide association studies revealed that AUXIN EFFLUX CARRIER PIN–FORMED LIKE 4 ( ZmPILS4 ) serves as a candidate gene underlying a major QTL of xylem traits. The near-isogenic lines (NILs) with lower expression of ZmPILS4 had 18–24% more auxin concentration in the root tips and 8–15% more xylem vessels. Nucleotide diversity values analysis in the promoter region suggested that ZmPILS4 was involved in maize domestication and adaptation. These results revealed the potential genetic basis of root anatomical plasticity during domestication. Abstract : Important chromosomal regions harbouring a candidate gene ( ZmPILS4 ) are involved in maize root anatomical plasticity and domestication, contributing to root-targeted breeding to improve environmental adaptation of maize.